Avaliação das ações de gestão associadas ao trabalho pedagógico das turmas de 3.º ano de escolas do município de Fortaleza no período pandêmico - Araripe, Milena Soares Bezerra Alencar (2023)
The research study entitled Evaluation of management actions associated with the pedagogical work of the 3rd year classes of schools in the city of Fortaleza during the pandemic period had the general objective of evaluating the implications of the results of management actions associated with the teaching practice of three schools in the network of Fortaleza, exclusively in the third year of elementary school classes of 2022, in the postCovid-19 pandemic period, through SAEF. The theoretical assumption was divided into three topics. The first on the History of Literacy, of which the theorists Geraldi (2015), Mortatti (2010) and Marcílio (2016) were essential to understand and discuss the historical process. The second topic, on Educational Assessment based on the authors Vianna (2000 and 2005), Luckesi (1996), Oliveira, Libâneo and Toschi (2012) and Bonamino and Sousa (2012). And the third and last topic on Management and pedagogical practice in literacy supported by the authors Vieira and Vidal (2015), Carneiro (2015) and Lück (2009). The methodology used is characterized by a qualitative nature, of an observatory nature, through field research through semi-structured interviews, carried out in the city of Fortaleza, circumscribed in the Education District II, in a sample of three teachers from the 3rd year of Elementary School and six professionals from the management core, including three pedagogical coordinators and three directors. It took place through semi-structured interviews, with data analysis supported by Bardin (1977) and Minayo (2015). Finally, in response to the general objective of this dissertation, we conclude that the actions of the interviewed managers, despite being extremely necessary and positive, do not dialogue with the results of the SAEF, that is, this external evaluation does not, in fact, subsidize their actions and pedagogical interventions.